Dietary Bacillus subtilis Supplementation Improves Intestinal Health of Meagre (Argyrosomus regius) Juveniles Fed Plant-Based Diets - Joana Oliveira; Raquel Ribeiro; Gabriela Gonçalves; Rafaela Santos; Cláudia Serra; Paula Enes; Pedro Pousão-Ferreira; Aires Oliva-Teles; Ana Couto (Journal of Marine Science and Engineering, 2025)
As aquaculture expands, plant-based feeds are increasingly used, but some fish species poorly tolerate them, affecting health and growth. Probiotics can help counter these effects by improving digestion, nutrient absorption, and immunity. This study evaluated the effect of dietary incorporation of Bacillus subtilis FI99 on the intestinal health of meagre. A nutritional challenge was performed with a practical control diet and three diets higher in plant-based ingredients: one without probiotic and two with probiotic incorporated at 1 × 109 CFU g−1 and 5.5 × 1011 CFU g−1. Histomorphological analysis was used to assess intestinal health and validate previously established machine learning models in predicting fish nutritional status. No differences were observed in zootechnical performance and biometric indexes. Most effects were observed in the anterior intestinal section, where probiotics improved total area, lumen area, lumen maximum diameter, total maximum diameter, villi area, and villi + lumen area. Additionally, probiotics improved supranuclear vacuole size, eosinophilic granulocytes, and intraepithelial leukocytes presence in anterior and intermediate sections. Machine learning models could not accurately predict the nutritional status of fish. Overall, the study indicates that dietary inclusion of B. subtilis enhances the intestinal health of meagre fed plant-based diets. Machine learning models require further development for improved accuracy.